THE EFFECTS OF VOCABULARY MASTERY AND SENTENCE STRUCTURE ON NARRATIVE WRITING SKILLS OF JUNIOR HIGH SCHOOL STUDENTS IN DEPOK - Sri Endar Retnowati; Effrina Yuricki (INFERENCE: Journal of English Language Teaching, 2019)
Abstract. The purpose of this study is to show that there are 1) the influence of mastery of vocabulary and sentence structure together on the ability to write narration of junior high school students in Depok, 2) the influence of vocabulary mastery on the ability to write narration of junior high school students in Depok, 3) the influence of mastery of structure sentence on the ability to write narration of junior high school students in Depok. The study was conducted at Al-Qalam SMPIT and Dharma Pertiwi Middle School in Depok .The selected population was IX grade students with a sample of 60 students using cluster sampling techniques. The results of this thesis study is There is a significant influence of mastery of vocabulary and mastery of sentence structure together on the ability to write narration of junior high school students in Depok. This is evidenced by the acquisition of Sig. 0.001 <0.05 and Fh = 8.517.Keywords: vocabulary mastery; sentence structure; narrative text; writing skills